2007
DOI: 10.1007/s10930-007-9078-z
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Serine Protease, Ba III-4, from Peruvian Bothrops atrox venom

Abstract: A serine protease from Bothrops atrox (Peruvian specimen's venom) was isolated in two chromatographic steps in LC molecular exclusion and reverse phase-HPLC. This protein was denominated Ba III-4 (33,080.265 Da determinated by MALDI-TOF mass spectrometry) and showed pI of 5.06, Km 0.2 x 10(-1 ) M and the V (máx) 4.1 x 10(-1 )nmoles p-NA/lt/min on the synthetic substrate BapNA. Ba III-4 also showed ability to coagulate bovine fibrinogen. The serine protease was inhibited by soyben trypsin inhibitor and DA2II, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
16

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 24 publications
0
7
0
16
Order By: Relevance
“…Proteolytic activity was assayed according to Gutiérrez et al (2008) and Ponce et al (2007) [69,70] with modifications. Briefly, 100 µg of venom protein and 500 µL of 2% ( w/v ) casein (Sigma-Aldrich) were diluted in 0.1 mM Tris–HCl (pH 7.4) and 0.15 M NaCl buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Proteolytic activity was assayed according to Gutiérrez et al (2008) and Ponce et al (2007) [69,70] with modifications. Briefly, 100 µg of venom protein and 500 µL of 2% ( w/v ) casein (Sigma-Aldrich) were diluted in 0.1 mM Tris–HCl (pH 7.4) and 0.15 M NaCl buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis by SDS-PAGE showed that TLBbar, has one band with ∼ 28.5 kDa, being a protein constituted of a single polypeptide chain (Figure 1(b) insert). TLBm of Bothrops marajoensis [9], Ba III-4 of Bothrops atrox [7], and PA-BJ of Bothrops jararaca [30] are serine proteases from snake venom that also have structure monomeric. Figure 2 shows the mass of TLBbar determined by mass spectrometry (ESI positive ionisation).…”
Section: Discussionmentioning
confidence: 99%
“…Snake venom serine proteases belong to trypsin S1 family clan SA. To date, a large number of studies, including molecular cloning, have led to the isolation and identification of TLEs mainly from the venom of subfamily Viperinaeand Crotalinae [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Anti-proteolytic activity. Proteolytic activity was determined using the synthetic chromogenic substrate Nα-benzoyl-DL-arginine p-nitroanilide (DL-BApNA), in 96-well plates, according to Ponce-Soto et al (14). BjuV or mixtures of BjuV and BFRE (1:1, 1:2, 1:3, w:w) were diluted with buffer (Tris-HCl, 10 mM, 10 mM CaCl 2 , 100 mM NaCl, pH 7.8) at 2 mg/mL.…”
Section: Methodsmentioning
confidence: 99%